Perkembangan Sosial Emosional Anak Usia Dini - malya yaya (Universitas muhammadiyah Banjarmasin, 2023)
The purpose of this study is to describe the social emotional development of early childhood. Social emotional development of a person begins when he is born into the world and is an important process in a child's life. This research uses qualitative research with Library Research approach.The problems of social-emotional development of early childhood that vary from difficulty socializing with others to excessive emotions when living socially are things that need to be considered so that continuity in life runs normally and accordingly. This is a lot of learning processes that do not encourage the progress of social emotional development of early childhood.Social-emotional development is one of the developments that should not be forgotten in addition to other developmental developments for early childhood. Because the true social-emotional development of a person stars from birth, so it is necessary for an educator to stimulate and support social-emotional development so that it is optimal.Humans grow and develop in a social environment, they interact with the environment. In this process of integration and interaction, emotional factors play an important role. This process is a process that places the child as a person who actively socializes and controls emotions.